Cow management capability based feed for local cow conservation in Aceh Besar - Nurhidayat Nurhidayat; Djufri Djufri; Abdullah Abdullah (Jurnal Edubio Tropika, 2018)
This study aims to determine the cow management based food carrying capacity as the conservation of local cattle in Aceh Besar. Data were collected in November 2016 s.d February 2017. Data collection was done with a technique cow management. Cow management data analysis performed by Chi Square. This study provides results that the cow management by breeder based on the level of education in Aceh Besar have good (if x2 count ≥ x2 tabel) at significant level of 5% with 7.81 degrees of freedom. the conclusion showed that the cow management base on food carrying capacity in the conservation efforts of local cow in Aceh Besar can be run properly.Keywords: Feed Management, Knowledge of breeders and Conservation Cow.